National Education Standards in Supporting Curriculum Development - Dewi, Mira Novia; Masritawati, Masritawati; Fatimah, Nurhayati; Asma, Siti (STIT Ahlussunnah Bukittinggi, 2025)
Education plays an important role in shaping a country's development, but Indonesia's current educational achievements have not yet reached an optimal level. As an investment in human resources, education, if managed properly, can have a significant impact on improving the welfare of society. However, issues related to education in Indonesia are very complex. The government has taken various steps to improve the quality of education and continues to strive to achieve this. Eight standards from the National Education Standards Agency (BSNP) have been used as the main reference in the implementation of education in Indonesia. Various policies have been made by adopting the contents of these standards. However, there are still many challenges that must be faced, such as the low quality of education that currently exists. The research approach used is library research, which is used to explore national education standards, their scope, and implementation strategies. This research is sourced from various references such as books, journals, articles, and data needed in this research. The objective is to gain an in-depth understanding of national education standardization. The results of this study indicate that content standards, learning processes, graduate competencies, education and teaching staff, facilities and infrastructure, and education management are integral parts of the National Education Standards (SNP). However, it is known that there are various obstacles that hinder their achievement. The main problems include inconsistencies in graduate competency standards, a lack of adequate facilities and infrastructure, limitations in the quality of education and teaching staff, and suboptimal education management in accordance with established standards.